Deleting exon 55 from the nebulin gene induces severe muscle weakness in a mouse model for nemaline myopathy - Ottenheijm, Coen Adri Charles; Buck, Danielle; de Winter, Josine M.; Ferrara, Claudia; Piroddi, Nicoletta; Tesi, Chiara; Jasper, Jeffrey R.; Malik, Fady I.; Meng, Hui; Stienen, Ger J. M.; Beggs, Alan H.; Labeit, Siegfried; et al. (Brain, 2013)
Nebulin—a giant sarcomeric protein—plays a pivotal role in skeletal muscle contractility by specifying thin filament length and function. Although mutations in the gene encoding nebulin (NEB) are a frequent cause of nemaline myopathy, the most common non-dystrophic congenital myopathy, the mechanisms by which mutations in NEB cause muscle weakness remain largely unknown. To better understand these mechanisms, we have generated a mouse model in which Neb exon 55 is deleted (NebΔExon55) to replicate a founder mutation seen frequently in patients with nemaline myopathy with Ashkenazi Jewish heritage. NebΔExon55 mice are born close to Mendelian ratios, but show growth retardation after birth. Electron microscopy studies show nemaline bodies—a hallmark feature of nemaline myopathy—in muscle fibres from NebΔExon55 mice. Western blotting studies with nebulin-specific antibodies reveal reduced nebulin levels in muscle from NebΔExon55 mice, and immunofluorescence confocal microscopy studies with tropomodulin antibodies and phalloidin reveal that thin filament length is significantly reduced. In line with reduced thin filament length, the maximal force generating capacity of permeabilized muscle fibres and single myofibrils is reduced in NebΔExon55 mice with a more pronounced reduction at longer sarcomere lengths. Finally, in NebΔExon55 mice the regulation of contraction is impaired, as evidenced by marked changes in crossbridge cycling kinetics and by a reduction of the calcium sensitivity of force generation. A novel drug that facilitates calcium binding to the thin filament significantly augmented the calcium sensitivity of submaximal force to levels that exceed those observed in untreated control muscle. In conclusion, we have characterized the first nebulin-based nemaline myopathy model, which recapitulates important features of the phenotype observed in patients harbouring this particular mutation, and which has severe muscle weakness caused by thin filament dysfunction.
Gesehen am 31.03.2022